BERASA: Media Interaktif untuk Mendukung Pemahaman Sinonim–Antonim pada Bahasa Indonesia Kelas 3 SD : Studi Kelayakan dan Kepraktisan - Nandita Camelia Putri; Fena Marlena; Marwah Azzahra Diani; Rani Setiawty (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
The purpose of this study is to create and assess the viability and usefulness of BERASA (Learning Synonyms and Antonyms in Indonesian), an interactive learning tool for third-grade elementary school students. Research and development using the ADDIE model—which comprises the phases of analysis, design, development, implementation, and evaluation—is the research methodology employed. Students from SDIT Al Kautsar Kudus in the third grade served as the study's subjects. While the practicality test was determined by teacher and student answers, the feasibility test was conducted by media and material specialists. According to the validation results, the BERASA media received a very feasible category feasibility rate of 91.6% from media experts and 88.8% from material experts. The results of the practicality test were 91.7% for teachers and 89.7% for students, both of which are classified as extremely appropriate. These findings indicate that the BERASA interactive learning materials are suitable and useful for teaching Indonesian, especially when it comes to synonyms and antonyms. They can also improve the comprehension and involvement of elementary school pupils.